Postprandial metabolic responses of serum calcium, parathyroid hormone and C-telopeptide of type I collagen to three doses of calcium delivered in milk - Marlena C. Kruger; Pamela R. von Hurst; Christine L. Booth; Barbara Kuhn-Sherlock; Joanne M. Todd; Linda M. Schollum (Journal of Nutritional Science, 2014)
Acute doses of Ca rapidly increase serum Ca and reduce bone resorption concomitant with a reduction in serum parathyroid hormone (PTH) levels. The physiological response to a dose of Ca in milk and to a Ca salt may be different. The present study investigated Ca absorption patterns with increasing levels of fortification in milk, and the response to one dose of a Ca salt. A group of twenty-eight Asian women aged 20–45 years volunteered to attend the laboratory over several weeks. The fasted volunteers were randomised to one of three experimental drinks: 200 ml skimmed milk containing 250, 500 or 1000 mg Ca. A subgroup of seven volunteers also received a calcium gluconate/carbonate salt containing 1000 mg Ca in 200 ml water. Serial blood samples and urine were collected for 5 h from baseline. Different doses of Ca in milk resulted in a graded response in serum corrected Ca, PTH and C-telopeptide of type I collagen (CTx) but not ionised Ca. Serum Ca increased in response to all milk drinks and from 2 to 5 h the blood Ca levels were significantly different for the 250 and 1000 mg doses, as was the integrated response between the loads. The PTH response to the two higher doses was significantly more than following the 250 mg dose. The integrated response for CTx and urinary Ca between all three doses of Ca in milk was significantly different. A dose of Ca salt elicited a more immediate response reaching a plateau faster, and declining faster to baseline. Fortified milk is a safe matrix for delivering larger doses of Ca.